MANAJEMEN KREATIF GURU PENGGERAK DALAM MENINGKATKAN KOMPETENSI PENERAPAN DISCOVERY LEARNING MELALUI IN HOUSE TRAINING (IHT ) - Endang Yunarti Farida; Rahmad Mulyono; Welius Purbonuswanto (STKIP Subang, 2022)
The background of this research is: 1) The teacher's low ability to choose and determine the learning model, the model applied is still traditional, teacher-oriented, and has not provided direct experience to students. 2) Teacher competence in applying the Discovery Learning model in learning is still low. The objectives of this study are: 1) To find out the steps of IHT in increasing teacher competence to apply the Discovery Learning learning model. 2) To find out the increase in teacher competence in applying the Discovery learning learning model through IHT. This study used the Kemmis and Targat model school action research design. The instruments or tools in this study used the instrument for examining the application of the Discovery Learning Model in lesson plans and the instrument for applying the Discovery Learning Model in learning which was used to assess teacher performance. There are two data obtained in this school action research: first, in the form of qualitative data in the form of a description of the implementation of the Discovery Learning Model in the lesson plans. Second, in the form of quantitative data in the form of values/numbers that describe the performance of teacher competence in the application of the Discovery learning model in learning through IHT. Based on the results of the research above, it illustrates that IHT can improve the ability of teachers to apply the Discovery Learning Model in learning. As for the data in the initial conditions, the average value was 1.90 in the